Dynamics of Land Use and Land Cover Changes in Keraniganj Upazila: Impacts of Rapid Urban Expansion near Dhaka City (Jagannath University Journal of Life and Earth Sciences, 2025)
Keraniganj Upazila, adjacent to Dhaka city, has experienced significant land use and land cover (LULC) changes over the past three decades due to rapid urbanization and socio-economic transformation. This study aims to investigate the spatial and temporal dynamics of LULC in Keraniganj from 1989 to 2023 and assess the driving factors and environmental implications of these changes. To achieve this, multi-temporal Lands at imagery, remote sensing (RS), and geographic information systems (GIS) techniques were applied, complemented by socio-economic data. Supervised classification algorithms were used to generate accurate LULC maps, and the results were validated using confusion matrices and Kappa statistics. The analysis covered six major LULC categories: bare land/sand fill, urban settlements, cultivated land, rural settlement/homestead vegetation, water bodies, and wetlands/lowlands. The results reveal a substantial increase of 1,738.62 hectares in urban settlements, particularly between 2009 and 2023, primarily at the expense of cultivated land, rural settlements, and natural ecosystems. During the study period, Keraniganj lost 476.46 hectares of cultivated land, 480.51 hectares of rural settlement areas, 1,087.83 hectares of water bodies, and 166.68 hectares of wetlands. These trends indicate extensive land reclamation, unplanned urban growth, and environmental degradation, driven by the area’s proximity to Dhaka, improved transportation infrastructure, and lower living costs. The findings underscore the urgency of implementing sustainable land use policies and integrated urban planning to address the negative impacts of urban expansion, including habitat destruction, reduced biodiversity, heightened flood risks, and declining agricultural productivity. This research contributes valuable insights into LULC dynamics and provides a replicable framework for monitoring and managing land transformation in rapidly urbanizing regions globally.Jagannath University Journal of Life and Earth Sciences, 10(1) 91-122